2015
DOI: 10.1017/s0025315415001915
|View full text |Cite
|
Sign up to set email alerts
|

Not all that clear cut: intraspecific morphological variability inSqualus blainville(Risso, 1827) and implications for identification of the species

Abstract: Of the three species of the genus Squalus that occur in the Mediterranean Sea, S. blainville and S. megalops are very difficult to distinguish. This study assesses the variability in morphological features that have been used to differentiate between these species. Squalus were collected from stations within the 25-nautical mile Fisheries Management Zone around the Maltese Islands; 349 specimens were dissected and categorized into male and female, mature and immature, and individuals were randomly selected fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 20 publications
1
27
0
Order By: Relevance
“…Both present and previous genetic data confirm that this taxon is widely distributed in the Mediterranean (Serena, 2005;Bat et al, 2005;Serena et al, 2009;Landi et al, 2014;Bonello et al, 2016;Kousteni et al, 2016;Cariani et al, 2017;Veríssimo et al, 2017).…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Both present and previous genetic data confirm that this taxon is widely distributed in the Mediterranean (Serena, 2005;Bat et al, 2005;Serena et al, 2009;Landi et al, 2014;Bonello et al, 2016;Kousteni et al, 2016;Cariani et al, 2017;Veríssimo et al, 2017).…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, it is reported that some common diagnostic morphological features, such as dermal denticles, teeth and dorsal fin spines could vary in shape with the onthogenetic development (White et al, 2013;Veríssimo et al, 2014). Consequently, the dermal denticles morphology should be further investigated before it can be properly used as a suitable classification tool, as also suggested by Bonello et al (2016) particularly for the genus Squalus.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations